2007
DOI: 10.1158/1055-9965.epi-06-0670
|View full text |Cite
|
Sign up to set email alerts
|

Risk for High-Grade Cervical Intraepithelial Neoplasia Associated with Variants of Human Papillomavirus Types 16 and 18

Abstract: Background: Although the variant lineages of human papillomavirus (HPV) types 16 and 18 are well established, their individual associations with high-grade cervical intraepithelial neoplasia (CIN) have not been extensively evaluated. Methods: Study subjects were women participating in the Atypical Squamous Cells of Undetermined Significance/ Low-Grade Squamous Intraepithelial Lesion Triage Study who were positive for HPV16 or HPV18 at enrollment. These women were followed every 6 months for 2 years. Viral isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
124
3
5

Year Published

2007
2007
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(151 citation statements)
references
References 52 publications
14
124
3
5
Order By: Relevance
“…This adds to the evidence from previous cohort studies showing that non-EUR HPV16 variants are more likely to persist and progress to CIN3þ than EUR HPV16 variants (13,17,25). Our findings suggest that there is additional stratification of risk within the HPV16 EUR lineage so that, among Danish women at least, variants containing 350T (including the HPV16 prototype) have a higher risk of persistence and progression to CIN3þ than those containing 350G.…”
Section: Discussionsupporting
confidence: 74%
“…This adds to the evidence from previous cohort studies showing that non-EUR HPV16 variants are more likely to persist and progress to CIN3þ than EUR HPV16 variants (13,17,25). Our findings suggest that there is additional stratification of risk within the HPV16 EUR lineage so that, among Danish women at least, variants containing 350T (including the HPV16 prototype) have a higher risk of persistence and progression to CIN3þ than those containing 350G.…”
Section: Discussionsupporting
confidence: 74%
“…HPV 16 variants, which vary by Յ2% from HPV 16 prototype nucleotide sequences, have been identified as the following six phylogenetic branches: European (E), Asian (As), Asian-American (AA), African-1 (Af-1), African-2 (Af-2), and northern American (NA) variants (18,52). Several researchers had reported correlations between specific HPV 16 variants and persistent viral infection, followed by the development of malignant lesions (3,4,16,37,43,49,50). Non-European variants were found to be associated with an excess risk of cervical cancer (37).…”
mentioning
confidence: 99%
“…These differences have been elucidated most clearly for HPV16. Multiple studies have shown that HPV16 variants differ in their association with cervical cancer (Tidy et al, 1989;Berumen et al, 2001;Zehbe et al, 1998aZehbe et al, , b, 2001Kammer et al, 2002;Xi et al, 2007), viral persistence (Grodzki et al, 2006;Xi et al, 2006;Lee et al, 2008) and the frequency of recurrence of cervical disease (Xi et al, 2007). Increased risk of anal cancers has also been reported for certain HPV16 variants (Xi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%